Applications of wireless sensor networks in pharmaceutical industry - Potdar, M.; Potdar, Vidyasagar; Sharif, Atif; Chang, Elizabeth (IEEE Computer Society, 2009)
Advances in wireless sensor networking have opened up new opportunities in healthcare systems. The future will see the integration of the abundance of existing specialized medical technology with pervasive, wireless networks. Radio frequency identification (RFID) and Wireless Sensor Network (WSN) are the two key elements of Pervasive computing and are considered as interrelated technologies. Although RFID has been used in various areas but it lacks intelligence that is its ability to process information and respond to real world events. People are using large scale WSN to monitor real-time environment status. RFID technology, if combined with other sensors, may enable a range of other applications that can exponentially increase visibility and monitoring. Combined with RFID a general sensor can be upgraded to intelligent wireless sensor (Smart node), having sensing, computation, communication into a single small device Field Programmable Gate Arrays (FPGA) With dazzling wireless technology now available, it's tempting for manufacturers to snatch up any wireless sensor that comes along as a means of optimizing processes and plant performance. This is especially true within the pharmaceutical industry, where vendors are plying industrial-strength wireless sensors for temperature, humidity and pressure, as well as sensitive process-monitoring wireless devices to support PAT applications. In this paper we surveyed the existing wireless sensor and RFID based technologies that target the healthcare application.